(untitled) (Pedagogy of Higher and Secondary Education, 2022)
In article conditions of increase spexmuenocnu training and education of schoolboys, and maxoece activily o school are opened during carrying out of employment (occupations) in educational branch “Technology”. Perspective opportuniries of labour training and development of the creative person in system of methods proects technologies are opened.